Madrasah Diniyah Takmiliyah (MDT) sebagai Pusat Pengetahuan Agama Masyarakat Pedesaan (Studi tentang Peran MDT di Desa Gapura Timur Gapura Sumenep) - Fathor Rachman; Ach Maimun ('Anil Islam: Jurnal Kebudayaan dan Ilmu Keislaman, 2016)
Madrasah Diniyah Takmiliyah (MDT) is a non-formal religious education which has been continuously striving to guide the Islamic religious education in the society, especially the younger generation, in an effort to strengthen their faith and piety in order to shaping mental-spiritual by taking into account the times. The study takes a role of MDT as a knowledge center for the main religion of rural communities, especially in Gapura Timur, Gapura Sumenep. This study used qualitative research-phenomenological approach. The data collected by purposive sampling. The data collection technique using participant observation, indepht interview and documentation. The data were analyzed using the interactive model analysis of Miles and Huberman done in the steps of data reduction, data display, and conclusion drawing or verification. The results of the research show that the existence MDT turned out to be a basic need for people to educate the religious teachings of the most basic as matters of faith, worship and akhlaqul karimah. The basic materials of Islamic religious education turned out to be especially important for people in an effort to strengthen the mental-spiritual people in the an identity crisis and a number of phenomena of decline the morality of the nation lately.